TRADITION OF FAMILY CHOICE IN THE 2024 PRESIDENTIAL AND VICE PRESIDENTIAL ELECTIONS: A STUDY ON STUDENTS OF THE FACULTY OF USHULUDDIN AND ISLAMIC STUDIES UIN NORTH SUMATRA CLASS OF 2021: TRADISI PILIHAN KELUARGA DALAM PEMILIHAN PRESIDEN DAN WAKIL PRESIDEN TAHUN 2024: STUDI PADA MAHASISWA FAKULTAS USHULUDDIN DAN STUDI ISLAM UIN SUMATERA UTARA ANGKATAN 2021 - Ulfah Fadillah Sidabalok; Elly Warnisyah Harahap (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2025)
This study aims to find out the extent of the influence of family choice traditions on students' political decisions in the 2024 Presidential and Vice Presidential Elections. This study uses a descriptive qualitative approach by collecting data through interviews and literature studies. The results show that the family is still the main political socialization agent that influences students' political preferences, mainly due to emotional bonds, economic dependence, and inherited values from an early age. However, technological advances, higher education, and political discussions in the campus environment also provide space for students to think critically and make political decisions independently. Thus, although the tradition of family choice is still strong, its influence on students' political decisions tends to begin to weaken with the development of the times and wider access to information.